1993
DOI: 10.1021/j100122a030
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of AlPO4-11 studied with x-ray powder diffraction and aluminum-27 and phosphorus-31 NMR

Abstract: The influence of water adsorption in AlP04-11 has been studied with X-ray powder diffraction and 27AI and 3IP NMR. With X-ray powder diffraction, a change of the crystal symmetry from ZMA2 to PNA2, is observed upon water adsorption, resulting in a diminished unit-cell volume and more elliptical pores. N M R was used to study the hydration on an atomic scale. With 27Al double rotation (DOR) and magic angle spinning (MAS) NMR, the quadrupole coupling constants (CQ) and asymmetry parameters (7) of the different A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 7 publications
8
83
0
1
Order By: Relevance
“…This process satisfies the conditions necessary to time-average both first-and second-order perturbations to the Zeeman interaction which have spatial dependences described by the second-and fourth-order Legendre polynomials, P 2 (cos b) and P 4 (cos b), respectively [1,2]. A number of studies have been reported utilizing DOR NMR for the differentiation of sodium, boron, aluminium and oxygen sites in minerals [9][10][11], materials [12][13][14][15][16] and molecular sieves, including, zeolites [17][18][19][20], sodalites [21][22][23] and aluminophosphates [24][25][26][27][28]. Recently, focus has turned to exploiting DOR for the study of oxygen sites in organic solids [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This process satisfies the conditions necessary to time-average both first-and second-order perturbations to the Zeeman interaction which have spatial dependences described by the second-and fourth-order Legendre polynomials, P 2 (cos b) and P 4 (cos b), respectively [1,2]. A number of studies have been reported utilizing DOR NMR for the differentiation of sodium, boron, aluminium and oxygen sites in minerals [9][10][11], materials [12][13][14][15][16] and molecular sieves, including, zeolites [17][18][19][20], sodalites [21][22][23] and aluminophosphates [24][25][26][27][28]. Recently, focus has turned to exploiting DOR for the study of oxygen sites in organic solids [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The inherently low sensitivity of NMR has also led to the application of satellite transition saturation/inversion signal enhancement techniques under DOR [16,17]. The majority of DOR NMR studies reported have been concerned with the differentiation of sodium, boron, aluminium and oxygen sites in minerals [18][19][20], materials [21][22][23][24][25] and molecular sieves, including, zeolites [26][27][28][29], sodalites [30][31][32] and aluminophosphates [33][34][35][36][37]. More recently, focus has turned to exploiting DOR for the study of oxygen sites in organic solids [17,[38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The different Al sites in the framework structure of calcined and hydrated AIPO4-11. [33] using five peaks with equal areas: four in the tetrahedral region and one at the octahedral position in agreement with the five distinct crystallographic sites derived from X-ray data [31]. These simulation results are not in agreement with those published by Barrie et al [34]; in that study, based on a questionable simulation of the 27A1 MAS NMR spectrum taken at 11.7 T, they concluded that all five crystallographic are partially hydrated to an equal extent.…”
Section: Op O Almentioning
confidence: 53%
“…From these results, it could be concluded that the broadening of the spectral DOR features is largely due to a dispersion in chemical shifts and neither due to heteronuclear dipolar coupling, nor to quadrupolar broadening [38]. It is important to notice that the formation of pentacoordinated aluminum upon water adsorption was not observed for fully hydrated A1PO4-11 samples [32,33,38]. From 27A1 DOR NMR experiments on dehyflrated A1PO4-5 Peeters et al [37] could detect three closely related T-sites (having quite the same CQ and [~u[ values) and so only little preferente for hydration of one particular aluminum site can be expected.…”
Section: Op O Almentioning
confidence: 90%
See 1 more Smart Citation